Pathophysiology of Aortic Aneurysms: Insights from Animal Studies - Khoury, Mitri K; Stranz, Amelia R; Liu, Bo (Cardiology and Cardiovascular Medicine, 2020)
Aortic aneurysms are defined as dilations of the aorta greater than 50 percent. Currently, the only effective treatment for aortic aneurysms is surgical repair, which is recommended only to those that meet criteria. There is no available pharmaceutical therapy to slow aneurysm growth and thus prevent lethal rupture. The development of a number of murine models has allowed in depth studies of various cellular and extracellular components of aneurysm pathophysiology. The identification of key therapeutic targets has resulted in several clinical trials evaluating pharmaceutical candidates to treat aneurysm progression. In this review, we focus on providing recent updates on developments in murine models of aortic aneurysm. In addition, we discuss recent studies of the various cellular and extracellular components of the aorta along with the abutting aortic structures that contribute to aneurysm development and progression.